A Brief Outline on Draft Annual Plan 1995-96 for Chief Minister - Deputy Chairman Planning Commission Level Discussions on 12th January, 1995 - Planning Commission (Planning Commission, Government of India, 1995)
The Draft Annual Plan 1995-96 for Himachal Pradesh presents a detailed developmental review of the state, tracing its administrative evolution, geographic features, demographic trends, and socio-economic profile. Formed in 1948 through the merger of princely states and attaining full statehood in 1971, Himachal Pradesh currently comprises 12 districts, 45 sub-divisions, 103 tehsils, 69 development blocks, and 2,757 Panchayats, reflecting a well-organized administrative framework. The state’s mountainous terrain spans altitudes from 350 to 6,975 meters, with diverse physiographic zones and rich water resources from perennial rivers like Yamuna, Sutlej, Beas, Ravi, and Chenab, offering significant hydropower potential estimated at 20,000 MW. Forests cover 66% of the land, although effective dense forest area remains limited, emphasizing conservation alongside development. According to the 1991 census, the population of 51.7 lakh exhibits a density of 93 persons per sq. km, with a high rural concentration (91.31%) and sex ratio of 976 females per 1,000 males. Literacy rates are rising rapidly, reaching 63.54% overall, with notable gender improvement. Scheduled Castes and Scheduled Tribes constitute 25.34% and 4.22% of the population, respectively. The state’s demographic trends indicate a declining population growth rate of 20.79% due to enhanced healthcare, literacy, and family planning initiatives. The report emphasizes the significance of human and natural resources, infrastructure planning, and equitable development across regions and social groups, providing a comprehensive foundation for the Annual Plan 1995-96 and future socio-economic strategies for the state.
Planning Commission Level Discussions on 12th January, 1995
Keywords: Himachal Pradesh; Population Growth; Administrative Structure; Physical Features; District Reorganization; Literacy Rate; Rural Development; Scheduled Castes; Scheduled Tribes; Hydropower Potential; Forest Resources; Demographic Trends